Analisis Kemampuan Berbicara di Depan Umum (Orasi) pada Tema 9 Kayanya Negeriku Subtema 3 Kelas IV di SD Negeri 3 Karangtalun - Palupi, Kristina Retno; Oktaviarini, Nourma (Pendagogia: Jurnal Pendidikan Dasar, 2024)
The purpose of this study is to describe the ability to speak in public (oration) on Theme 9 Kayanya Negeriku Subtheme 3 class IV at SD Negeri 3 Karangtalun. This type of research is qualitative with a phenomenological approach. The collection in this study used observation, interviews and documentation. The results of this study can be stated that students who are included in the very capable category there are 2 students, namely RN and R students with a score of more than 86. Students who are included in the capable category there is one student, namely CWN students with a score of 70-85. There are 4 students who are included in the Moderately capable category, namely RJ, RF, RGR and SR students with scores between 56-70. RJ's observation results obtained a total score of 16 with a score of 57.1. There are 3 students who are included in the underprivileged category, namely DF MB and PA students.